Hubungan Kondisi Institusional dengan Niat Petugas untuk Menggunakan Rekam Medis Elektronik di Rumah Sakit X - Adinda Mentari Nursya’bani; Daniel Happy Putra; Dina Sonia; Muhammad Fuad Iqbal (STIKes Ibnu Sina Ajibarang, 2024)
The implementation of electronic medical record (EMR) in institutions that are ready will have a positive impact on its execution. Institutional readiness should be comprehensively assessed across various aspects, including human resources. Users are a key factor in determining the success of an information system. User feedback can serve as a consideration to maximize EMR implementation. However, this can sometimes be unpredictable due to numerous influencing factors, including institutional conditions. To explore the relationship between institutional conditions and the intention of healthcare providers to use EMR, a quantitative inferential study with a cross-sectional design was conducted at Hospital X. The study population consisted of 129 healthcare providers, with 91 data points processed as samples. Data were analysed using univariate and bivariate analyses with the Chi-Square test. Among the 91 analysed data points, institutional conditions were categorized as good (56%), intention to use EMR was high (56%), and use behaviour was high (82,4%). There was a significant relationship between institutional conditions and healthcare providers’ intention to use EMR, with a p-value of 0,001 < 0,05 and an Odds Ratio of 4,908.